Effect of paint baking treatment on microstructure and properties of 6082 aluminum alloy CMT welded joints filled with AlSi10Cu2Mg0.7Zn1 wire - Chunguo Fu; Shiwei Xu; Shuhan Yang; Xuan Zhu; Xiaoyi Yang; Mengnie Victor Li (Journal of Materials Research and Technology)
Aluminium alloy 6082-T6 is known for its high strength and cost effectiveness, making it a popular choice for thin sheet structures such as automotive body panels. However, the welding-induced softening of the heat affected zone (HAZ) and the insufficient strength of the filler metal are the primary factors limiting its broader application. In this study, the lower heat input cold metal transfer welding method is employed, utilizing heat-treatable reinforced AlSi10Cu2Mg0.7Zn1 wire to weld 6082-T6 plates. Additionally, the impact of the baking paint process within the automotive manufacturing workflow on the evolution of microstructural characteristics of the HAZ and Weld Zone (WZ), as well as the mechanical properties of the joints, is investigated in detail. The findings indicate that the AlSi10Cu2Mg0.7Zn1 filled WZ contains a small quantity of θ, Q, and β phases, alongside a significant amount of reticulated eutectic Si distributed among the Al dendrites. Notably, the strength of the WZ is enhanced compared to that of conventional Al–Si and Al–Mg wires. During the baking process, the WZ exhibits the precipitation of a small amount of fine β’’ and β′ precipitates, which elevates the tensile strength of the WZ to 272 MPa and the yield strength to 179 MPa. Furthermore, the baking treatment promotes the further growth of β′ in the HAZ of the joints, while fine β’’ phases are reprecipitated within the Al matrix. The combined influence of these two precipitated phases results in an increase in the tensile strength of the HAZ by 29 MPa.